2022
DOI: 10.3390/su14031108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Groundwater Storage Depletion Using GRACE/GRACE Follow-On Data with Land Surface Models and Its Driving Factors in Haihe River Basin, China

Abstract: Groundwater storage (GWS) in the Haihe River Basin (HRB), which is one of the most densely populated and largest agricultural areas in China, is of great importance for the ecosystem environment and socio-economic development. In recent years, large-scale overexploitation of groundwater in HRB has made it one of the global hotspots of GWS depletion. In this study, monthly GWS variations in HRB from 2003 to 2020 were estimated using the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow-On (GRACE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…However, we note it is the trend of groundwater‐level in December instead of the annual average field like OBS1 or GRACE results. Similar behavior is reported in a recent study (Guo et al 2022), which also indicates a sharp increase in the deep groundwater funnel area from 2014 to 2020. Although the implementation of the SNWDP in 2014 facilitate the transformation of the previous water use mode into a conjunctive use of surface water and groundwater, the decreasing GWSA during the end of period II illustrates a greater water demand under a dry climate, which cannot be effectively addressed solely using the surface water (e.g., diverted water and precipitation).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, we note it is the trend of groundwater‐level in December instead of the annual average field like OBS1 or GRACE results. Similar behavior is reported in a recent study (Guo et al 2022), which also indicates a sharp increase in the deep groundwater funnel area from 2014 to 2020. Although the implementation of the SNWDP in 2014 facilitate the transformation of the previous water use mode into a conjunctive use of surface water and groundwater, the decreasing GWSA during the end of period II illustrates a greater water demand under a dry climate, which cannot be effectively addressed solely using the surface water (e.g., diverted water and precipitation).…”
Section: Resultssupporting
confidence: 91%
“…A recent study argued that shallow unconfined groundwater remained stable during 2015 to 2017 and the deep confined groundwater decreased much faster than that before 2014 via the independent component analysis (ICA) and multisource data (Li et al 2021). Guo et al (2022) also confirmed this statement according to the groundwater‐level records from confined wells over the NCP. Similar behaviors are also detected based on continuous downscaled GRACE GWSA, resulting in the decreasing trend of −19.11 ± 8.75 and −19.72 ± 9.08 mm/a during the period 2015 to 2020.…”
Section: Discussionmentioning
confidence: 71%
“…There were successful studies calculating the GWS change in arid regions based on GRACE\GFO data [ 55 , 61 , 62 , 63 , 64 , 65 ]. Like most studies, the GWS changes in Inner Mongolia were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The most representative GWS change monitoring methods include groundwater level fluctuation method (WTF), hydrological model [5], groundwater flow model [6] and satellite gravity measurement [7]. However, the use of monitoring wells to measure groundwater levels requires a sufficient number of monitoring points and a reasonable distribution.…”
Section: Introductionmentioning
confidence: 99%